POLICING IN MULTI-ETHNIC COMMUNITY (MACEDONIAN CONDITIONS) - Angeleski, Metodija; Gjorgieva, Aleksandra; Bozaroski, Anton; Simonovska, Sanja; Gaberova, Nikolina; Nedelkovska, Martina (European Scientific Journal, ESJ, 2014)
The late 20th and the early 21th century started to push on and implementation decentralized proactive policing in draft model of community policing the first in highly developed countries and later gradually on countries in development. This model not includes only fight against crime but also deal with any security problems at the local community level so that you can rightfully say that it is modern concept of security on strategic principles and prevention programs. The long road to Euro-Atlantic integration Macedonian police this trend of modern policing is still making strides to become a reality. The extent of integration on the police in society and interaction was perceived as well exchange of information with local community in this case we need empirical research for resolving on the security issues. Such a one research recently was completed in Macedonia but research conducted from student team of FON University. The results show that the integration of the Macedonian police in ethnically mixed areas, and that citizens have confidence in police officers with their different nationalities.